Improving population levels of physical activity through integration into everyday life: a before and after analysis of the Cycling City and Towns programme. (November 2016) - Stewart, Glenn; Anokye, Nana; Pokhrel, Subhash
Abstract: Background: Population levels of physical activity are far too low to maximise health. In 2008, the Cycling City and Towns (CCT) programme was instigated across 12 cities and towns in England with the aim to get more people cycling "more often, more safely" through a whole-town approach to cycling. The aim of this study was to assess the effect of CCTs on utility (transport) cycling and other types of physical activity. Methods: In this quasi-experimental study, population cycling and other physical activity behaviours in CCTs were compared with that in their closest corresponding city and towns, as defined by the Office for National Statistics (ONS). Data were taken from the annual Active People Survey, a geographically representative survey of all English local authorities with about 165 000 respondents providing information on their utility cycling, sport, and active recreation behaviours in the past 28 days. Logistic regression was estimated to identify the effect of CCTs on utility cycling and sport or active recreation, allowing for the potential interaction effects of time trends in national cycling prevalence. Findings: A general decline in cycling for transport purposes was observed in both areas. With adjustment for time trends and other confounding, CCTs were associated with an increased probability of transport cycling compared with comparison areas (odds ratio 1·48, 95% CI 1·14–1·94). The effect of CCTs on other forms of physical activity was not significant (0·94, 0·84–1·04). The male population, individuals aged 16–34 years, and people in the ONS socioeconomic category NS SEC 9 were most likely to have cycled. Those least likely to cycle were those in categories NS SEC 5–8 and of Asian ethnicity. Interpretation: Despite the decline in transport cycling nationally, CCTs appear to be an effective intervention to promote cycling for transport purposes. Importantly, this effect does not seem to have come through a substitution of physical activity undertaken through sport or active recreation. However, more research is needed to address some limitations of our analysis, specifically the unobserved differences between areas obtaining CCT funding and other regions. Funding: None.